The Effect of Channa striatus (Haruan) Extract on Pain and Wound Healing of Post-Lower Segment Caesarean Section Women. (25th May 2015) - Ab Wahab, Siti Zubaidah; Abdul Kadir, Azidah; Nik Hussain, Nik Hazlina; Omar, Julia; Yunus, Rohaizan; Baie, Saringat; Mohd Noor, Norhayati; Hassan, Intan Idiana; Wan Mahmood, Wan Haslindawani; Abd Razak, Asrenee; Wan Yusoff, Wan Zahanim
Abstract : Channa striatus has been consumed for decades as a remedy to promote wound healing by women during postpartum period. The objectives of this study were to compare postoperative pain, wound healing based on wound evaluation scale (WES), wound cosmetic appearance based on visual analogue scale (VAS) scores and patient satisfaction score (PSS), and safety profiles between C. striatus group and placebo group after six weeks of lower segment caesarean section (LSCS) delivery. A randomised, double-blind, placebo-controlled study was conducted. Subjects were randomised in a ratio of 1 : 1 into either the C. striatus group (500 mg daily) or placebo group (500 mg of maltodextrin daily). 76 subjects were successfully randomised, with 38 in the C. striatus group and 35 in the placebo group. There were no significant differences in postoperative painp = 0.814 and WESp = 0.160 between the C. striatus and placebo groups. However, VAS and PSS in the C. striatus group were significantly better compared with the placebo group (p = 0.014 andp < 0.001, resp.). The safety profiles showed no significant differences between the groups. In conclusion, six-week supplementation of 500 mg of C. striatus extract showed marked differences in wound cosmetic appearance and patient's satisfaction and is safe for human consumption.